The role of the state in shaping zero hours work in an atypical liberal market economy. (August 2020) - O'Sullivan, Michelle; Turner, Thomas; Lavelle, Jonathan; MacMahon, Juliet; Murphy, Caroline; Ryan, Lorraine; Gunnigle, Patrick; O'Brien, Mike
Zero hours work typifies work where there are no guaranteed hours offered by the employer. This article examines the relationship between the state and the emergence of zero hours work in an atypical liberal market economy, Ireland. Based on interviews with informed stakeholders with a focus on four sectors – retail, health, education and accommodation/food – the article concludes that the actions of the state have created a weak regulatory environment that has facilitated the emergence of zero hours work. The findings are discussed with a theoretical frame using the concepts of accumulation and legitimation.